Tractor performance and corn crop development as a function of furrow opener and working depth in a Red Latosol - Bertonha, Rafael Scabello [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP]; Silva, Vicente Filho Alves; Wright, David L. (My University, 2015)
To use a no-tillage system, the producer must know the ideal tool for each condition encountered in the soil. In seeding, the function of the furrow opener is loosening and disturbing the soil, but if the opener lacks the specific geometry for a specific soil condition, the furrow opening angle could be incorrect, leading to compaction due to mirror formation on the walls of the furrow. The aim of this study was to analyze three hoe-type furrow openers of planters at different working depths, evaluating the area of disturbed soil, tractor performance, and corn crop yield. The experiment was conducted in areas of the UNESP/FCAV, Brazil on a soil classified as a Eutroferric Red Latosol. A randomized block design with factorial scheme 3 × 5 (three shanks: FO1, FO2, and FO3, and five depths: WD1, 6.0; WD2, 9.5; WD3, 10.5; WD4, 12.0; and WD5, 13.5 cm), with four replications was used. The results showed that the soil disturbance was highest at working depths of WD3, WD4, and WD5. With WD1 and WD2, the emerged seedlings began the crop cycle in fewer quantities (72839 and 73380 plants ha-1, respectively). The final stand of the crop, corn-grain yield, and biomass were not affected by the treatments. The opener with greatest tip angle (29°) showed a lower traction power demand and fuel consumption than openers with 27° and 17° at working depth WD5, and in general, incurred higher fuel consumption per volume of soil disturbance. Opener geometry and soil type directly affect soil disturbance, machine performance, and crop development. However, in this study, we suggest the opener with a rake angle of 27°, working at greater depth, because this combination provided better fuel consumption per volume of disturbed soil and no reduction of crop productivity.
Keywords: Agricultural machines; Disturbed area; Grain yield; Groove loosening; Shank; Zea mays L